ANALISIS RESERVOIR KOMPARTEMEN BERTENAGA PENDORONG TUDUNG GAS DENGAN MENGGUNAKAN PERSAMAAN MARHAENDRAJANA â BLASINGAME - Restu Fairuz, Ajeng
In highly faulted reservoir system, lateral connectivity is a very important factor to explain the fluid flow connectivity, and becoming principal understanding in the further plan and development. By understanding the lateral connectivity of reservoir, improved and enhanced recovery methods can be maximized for oil recovery. Static data such as seismic and logging can determine the fault location and geometry of the reservoir divided into several compartments, but it can not be known flow connectivity between compartments. Fluid flow connectivity can be determined from dynamic data as well test data and production data. Well test data is very expensive and only available in some wells, while the production data are available for all wells and can be compared with log data. The objective of this final project is to determine the fault conditions of reservoir with gas cap driving mechanism based on flow connectivity by using production data. As for research methods to perform reservoir modeling by using PETREL and ECLIPSE software. The expected result is the tendency of chart patterns that can predict fracture conditions in the reservoir with gas cap driving mechanism.